Bethabara Moravian Church. - (:unkn) unknown (Forsyth County Public Library, 2009)
Photo made in the 1930s.
Bethabara Moravian Church.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth